Hip-hop, identity, and conflict: Practices and transformations of a metropolitan culture - Benvenga, Luca (Frontiers in Sociology, 2022)
In this paper, I expose how it is possible to investigate the hip-hop culture on three levels of analysis—historical, semiotic, and phenomenological—precisely as theorized by Cohen (1997) for his study on modern subcultures. The analysis will focus on the hip-hop of the beginning, since the middle of the Seventies and Eighties in the United States, but then it will broaden to a reflection on its diffusion and re-invented, with particular reference to the interactions with the globalization and the changes occurred in contemporary metropolis. In this sense, considering hip-hop as a subculture in the following pages, I reflect (a) on the origin of rap music, its interrelation with the Afro-American culture and the concept of blackness which it conveys. Subsequently, I clarify (b) that the art of writing, in the form of Tag, and break dance have certificated the presence of young people from the United States outskirts, and then the passage to a precise historical moment. Finally, I try to demonstrate (c) that today, a different dimension of hip-hop is implemented, whose features have changed in parallel with the transformations that have affected the metropolis and the youth cultures. These last one are increasingly hybrid and involved in a recreational, market system, where the changing nature of hip-hop allows: its enormous success, with the domain of the musical market and other assimilation processes, such as clothing, which have contributed to its mutation in a global culture, some margins of autonomy.